Peningkatan Perekonomian Mahasiswa Melalui Tekno Pangan: Pembuatan Jamu Beras Kencur - Rio Janto Pardede; Yatmini Yatmini; Gunaryo Sudarmanto; Manintiro Uling; Zummy Anselmus Dami (Abdimas Universal, 2023)
The training on the production of herbal rice kencur is a simple training, with a small capital but has big benefits. And the herbal rice kencur has very good benefits for health. The students of the Indonesian Bible Institute are students who come from various cities in Indonesia, even herbal rice kencur is something new for them. The training method used is the delivery of materials and direct assistance from manufacture to marketing. The production of herbal rice kencur is very attractive to students, it can be seen from the conclusion of the questionnaire that became the evaluation material. The results showed: 1) The training on the production of herbal rice kencur was very beneficial for the participants, 2) Besides being easy and cheap to manufacture, the production of herbal medicine for rice kencur has a good market and many enthusiasts, 3) The profits from the production of herbal medicine for rice kencur are very promising, 4) The manufacture of herbal rice kencur can open up personal business and employment opportunities for people who are in economic difficulty. 5) Input to the Joshua Ministry and to the Indonesian Gospel Institute to continue to produce herbal rice kencur production activities to equip students.